Solve the simultaneous equation: 2x + 3y = 6, 3x + 2y = 5.

  • Google+ icon
  • LinkedIn icon
  • 723 views

1) 2x + 3y = 6

2) 3x + 2y = 5

We can either use substitution or elimination.

Using elimination:

Multiply equation 1) by 3 and multiply equation 2) by 2.

1) 6x + 9y = 18

2) 6x + 4y  = 10

Equation 1) - Equation 2)

5y = 8

y = 8/5

Substitue y back into either 1) or 2).

6x + (32/5) = 10

6x = 10 - (32/5)

x = 3/5

Aaquib N. A Level Maths tutor, GCSE Maths tutor

About the author

is an online GCSE Maths tutor with MyTutor studying at Birmingham University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss

mtw:mercury1:status:ok